2009
DOI: 10.1242/dev.032631
|View full text |Cite
|
Sign up to set email alerts
|

The PGD2 pathway, independently of FGF9, amplifies SOX9 activity in Sertoli cells during male sexual differentiation

Abstract: Activation by the Y-encoded testis determining factor SRY and maintenance of expression of the Sox9 gene encoding the central transcription factor of Sertoli cell differentiation are key events in the mammalian sexual differentiation program. In the mouse XY gonad, SOX9 upregulates Fgf9, which initiates a Sox9/Fgf9 feedforward loop, and Sox9 expression is stimulated by the prostaglandin D2 (PGD2) producing lipocalin prostaglandin D synthase (L-PGDS, or PTDGS) enzyme, which accelerates commitment to the male pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
162
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 162 publications
(170 citation statements)
references
References 39 publications
5
162
1
2
Order By: Relevance
“…Nevertheless, regardless of speculation on this somatic role, our results suggest that goat SRY may have functions other than up-regulating SOX9, at least in non-Sertoli somatic cells. As for the second question, as it has been shown in mice that the maintenance of Sox9 expression requires two independent positive feed forward loops, one engaging Fgf9 and Fgfr2 (Kim et al, 2006;Bagheri-Fam et al, 2008;Hiramatsu et al, 2010), and the other Pgds and PGD2 (Wilhelm et al, 2005;Moniot et al, 2009), so we tried to evaluate these pathways in the goat. Of interest, FGFR2 was found to be expressed specifically in differentiating Sertoli cells at the time of SOX9 up-regulation.…”
Section: Primary Expression Time Of Switchingmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, regardless of speculation on this somatic role, our results suggest that goat SRY may have functions other than up-regulating SOX9, at least in non-Sertoli somatic cells. As for the second question, as it has been shown in mice that the maintenance of Sox9 expression requires two independent positive feed forward loops, one engaging Fgf9 and Fgfr2 (Kim et al, 2006;Bagheri-Fam et al, 2008;Hiramatsu et al, 2010), and the other Pgds and PGD2 (Wilhelm et al, 2005;Moniot et al, 2009), so we tried to evaluate these pathways in the goat. Of interest, FGFR2 was found to be expressed specifically in differentiating Sertoli cells at the time of SOX9 up-regulation.…”
Section: Primary Expression Time Of Switchingmentioning
confidence: 99%
“…Consequently, the first steps of testis differentiation appear to be straightforward in the mouse: pre-Sertoli cells specifically express SRY that directly activates transcription of the Sox9 gene (Sekido and Lovell-Badge, 2008). Once SOX9 is up-regulated in the Sertoli cells, its expression is maintained by at least two positive feedback loops, one that involves Fgf9 and its receptor Fgfr2 (Kim et al, 2006;Bagheri-Fam et al, 2008;Hiramatsu et al, 2010), and the other which acts through the Pgds gene and its by-product PGD2 (Wilhelm et al, 2005;Moniot et al, 2009). Concomitantly to the maintenance of Sox9 expression, Sry expression declines and then disappears completely after seminiferous cord formation at around 12.5 dpc (Wilhelm et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These self-activating mechanisms amplify Sox9 expression and activity during mammalian testicular organogenesis and work in seemingly independent fashions. [10] As discussed below, such elementary circuits involving positive feedback loops are sufficient to maintain a differentiated state and in the case of Sox9 the existence of redundant circuits can be interpreted as a fail safe against the effects of (potentially sex-reversing) mutations in one of the branches of the network.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, recent genetic studies have indicated that SOX9 can bind to the conserved SOX-binding site within the L-Ptgds gene promoter region and control the onset expression of L-Ptgds (Wilhelm et al 2007a,b). Moreover, conditional deletion of Sox9 in Sertoli cells also dramatically downregulates the L-Ptgds in the mutant XY gonads, indicating that maintenance of L-Ptgds is also dependent on SOX9 (Moniot et al 2009). Taken together, PTGDS/PGD 2 signaling pathway forms a positive regulatory feedback loop with the Sox9 gene, whereby PGD 2 can reinforce the expression of Sox9 during the later stage of sex determination and SOX9 can initiate and maintain the L-Ptgds gene expression.…”
Section: Prostaglandin D Synthase/pgd 2 Signalingmentioning
confidence: 97%
“…L-Pgds-knockout XY mouse gonads show a significantly reduced expression level of Sox9, abnormal nuclear translocation of SOX9, and a delay in testicular organogenesis (Moniot et al 2009). Autocrine or paracrine PGD 2 signaling, independent of FGF9-mediated signaling, can act as an amplification system of Sox9 expression, promoting the nuclear localization of SOX9 via its cAMP-PKA phosphorylation and initiates subsequent Sertoli cell differentiation (Malki et al 2005, Moniot et al 2009). …”
Section: Genes Implicated In the Regulation Of Sry Expressionmentioning
confidence: 99%